Rectangular flaps technique for treatment of congenital hand syndactyly - Tuma Jr., Paulo; Arrunategui, Gino; Wada, Alexandre; Friedhofer, Henri; Ferreira, Marcus Castro (Revista do Hospital das Clínicas, 1999)
The authors analysed a series of 22 patients undergoing surgical correction of congenital hand syndactyly by the rectangular flap technique. Using our evaluation method, we found that good functional and aesthetic results were obtained in 77.3% of the patients, with a complication rate of 13.6%. We concluded that the rectangular flap technique has a simple design, is easily reproducible by in-training staff, has good results, and can be applied on the majority of the syndactyly cases.